Conformance Testing of Cyber-Physical Systems: A Comparative Study - Mohaqeqi, Morteza; Mousavi, Mohammad Reza; Taha, Walid (Electronic Communications of the EASST, 2014)
<!–StartFragment–>For systematic and automatic testing of cyber-physical systems, in which a set of test cases is generated based on a formal specification, a number of notions of conformance testing have been proposed. In this paper, we review two existing theories of conformance testing for cyber-physical systems and compare them. We point out their fundamental differences, and prove under which assumptions they coincide.